241 ORAL ALKALI REDUCES URINE ENDOTHELIN EXCRETION IN CHRONIC KIDNEY DISEASE ASSOCIATED WITH PRIMARY HYPERTENSION. (1st January 2006) - Phisitkul, S.; Simoni, J.; Wesson, D. E.
Abstract : Purpose: Renal endothelin 1 (ET-1) production is increased in the 5/6 nephrectomy experimental model of chronic kidney disease (CKD) and in rats with normal GFR ingesting mineral acid or acid-producing dietary protein. Unpublished data from our laboratory support that amelioration of the acid retention in experimental CKD with dietary alkali decreases renal ET-1 production as measured by urine excretion of endothelin 1 (UET-1 V). We hypothesized that the same is true in human CKD. Methods: We recruited 18 healthy controls, 21 subjects with primary hypertension without CKD, and 19 subjects with CKD (plasma creatinine 1.5-6.0 mg/dL) and primary hypertension without diabetes, evidence of glomerulonephritis, or history of renal replacement therapy. We reduced systolic blood pressure (SBP) in the latter 2 groups toward 130 mm Hg over 6 months. We then prescribed oral Na + citrate to CKD subjects with TCO2 < 22 mM (n = 12) but not to those with TCO2 22 mM (n = 7) and followed each for an additional 6 months. We measured UET-1V (ng/g creatinine or ng/g Cr) in a spot am specimen and venous blood TCO2 at 0, 6, and 12 months. Summary: UET-1V was higher than healthy controls (3.1 6 0.4 ng/g Cr) in hypertensives without CKD (5.9 6 1.1 ng/g Cr, p < .03 vs controls) and in hypertensives with CKD (5.1 6 0.7 ng/g Cr, p < .02 vs controls). After SBP reduction, UET-1V in hypertensives without CKD (3.5 6 0.4 ng/g Cr) was not different from healthy controls (p = .23) but that for hypertensives with CKD (5.3 6 0.5 ng/g Cr) remained higher than control (p < .001) and was now higher than hypertensives without CKD (p < .007). TCO2 increased in CKD subjects prescribe Na+ citrate (20.1 6 0.4 to 23.9 6 0.4 mM, p < .001 paired t) but decreased in those not prescribed Na+ citrate (23.6 6 0.5 to 23.0 6 0.5 mM, p < .03 paired t). Although UET-1V was not different between CKD subjects before Na+ citrate (p = .85), UET-1V decreased in those prescribed Na+ citrate (5.4 6 0.6 to 4.1 6 0.4 ng/g Cr, p < .02, paired t) but did not change in those not prescribed Na+ citrate (5.2 6 1.0 to 6.1 6 1.0 ng/g Cr, p = .10, paired t). Follow-up UET-1V was lower in CKD subjects prescribed compared to those not prescribed Na+ citrate (p < .04). Conclusions: The data show that primary hypertensives with compared to those without CKD have higher UET-1V despite improved BP control that is decreased by oral Na+ citrate. These studies support the contention that subjects with CKD have increased renal ET-1 production that is mediated by the associated positive acid balance.